Fa‘āliyyah Istikhdām Wasīlah al-Takhmīn li-al-Kalimāt ‘alā Kafā’ah al-Mufradāt al-‘Arabiyyah li-Ṭālibāt Ma‘had al-Walī Songo Cukir Jombang Jāwī al-Syarqiyyah - Tri Nur Fauziyah, Tri Nur; Qomariyah, Lailatul (Program Studi Pendidikan Bahasa Arab, 2023)
This paper examined 1) how to use a word guesser at the Wali Songo Cukir Jombang Javi Oriental Institute? 2) how efficient is the Arabic vocabulary of the students of the Wali Songo Cukir Jombang Javi Oriental Institute? 3) How effective is the use of the guessing method of words on the efficiency of the Arabic vocabulary of the students of the Wali Songo Cukir Jombang Java Oriental Institute? A method of this research is quantitative research with the type of research that is correlated and collected data with questionnaires and testing. and then analyzed by paired sample. The results of this research are: 1) The use of the guessing method for words at the Wally Sonja Institute is scheduled every day at night. That is, the teacher reads the vocabulary and then the students listen and imitate the vocabulary and the teacher gives the meaning of the word. This method is repeated until the students have mastered the word. 2) The vocabulary competence of the students at the Walli Songo Institute is at an advanced level. It is evident from the results of the test on the efficiency of the Arabic vocabulary for female students. In the pre-test only 4 students reached KKM. Then the post-test increased to 19 out of a total of 20 female students. 3) The effectiveness of the use of word guessing and vocabulary competence for female students at the Walisongo Institute. This data is known from the results of testing the hypotheses using the validity of the experts by looking at the value before and after the application of the guessing method for the words obtained with a value of SEC 004,0 (004,0 Sig ) which has a certain (Ha )acceptable (H0 ) yielded, which indicates the presence of a stuck between the metric and metric, meaning that there is efficacy between the use of a word guesser on vocabulary competence.